Beta phase formation of polypropylene with bentonite filler - Lozano, Tomás; Morales, Ana Beatriz; Lafleur, Pierre G.; Cerino Córdova, Felipe de Jesús; Laria, Julio; Salas, Homero; Barragán, Rodolfo; Pichardo, Roberto (Universidad Autónoma de Nuevo León, 2012)
In this paper, a study on Polypropylene (PP)/bentonite composites is presented, PP/bentonite composites were prepared using 5%, 10% and 25% on concentration in weight of unmodified and modified bentonite filler. The relative level of the beta phase of the samples was calculated using Wide Angle X-ray Diffraction (WAXD). Differential scanning calorimeter (DSC) was used to observe the melting and crystallization behaviour of the samples. The dispersion state of the composites was observed using optical microscopy. The obtained results show the possibility of inducing the beta phase in PP material using bentonite as filler. However, only the composites of polypropylene with modified bentonite showed the beta signal and higher content was at 10% of filler. Although at 10% of modified bentonite the dispersion is worse than in 5%, at 10% there are more nucleating sites for beta phase formation and consequently more beta content. However, as concentration of the filler increases to 25%, the nucleating sites also increase but its dispersion into the compound becomes worse which strongly decreases the beta phase formation.